Recommendations for breast cancer education for African American women below screening age. Issue 5 (16th September 2021) - Huq, M R; Woodard, N; Okwara, L; McCarthy, S; Knott, C L
Abstract: Although statistically unlikely, early-onset breast cancer tends to be more aggressive and leads to greater mortality than breast cancer among women of screening age. Young African American women are disproportionately impacted by early-onset breast cancer compared to women of other races. Given the racial disparities and because young women are typically not the primary audience for breast cancer educational messaging, there is a need to identify recommendations for age-appropriate breast cancer education for African American women below mammogram eligibility. Through N  = 30 key informant interviews with young African American breast cancer survivors, family members of young survivors, community organization leaders and healthcare providers, we identified breast cancer educational message content and communication channels relevant for these women. Participants recommended that message content should emphasize the need to address family cancer history and self-advocacy in healthcare encounters in addition to concerns about loss of womanhood, financial costs and opportunity costs associated with preventive healthcare visits. Breast cancer messages for this audience should consider the influences of earlier life stage, culture and race. Recommended communication channels highlighted use of social media and videos. Findings will inform future age-appropriate educational messaging aimed at eliminating early-onset breast cancer disparities disproportionately impacting young African American women.